Perlindungan Hukum Mahasiswa Magang Terhadap Praktik Unpaid Internship Perspektif Hukum Ketenagakerjaan Indonesia - Irene Mariboto Sitanggang (Media Hukum Indonesia (MHI), 2026)
Internship programs aim to provide students with work experience; however, the practice of unpaid internships remains widespread and has the potential to harm participants. This study employs a normative legal approach by examining labor regulations in Indonesia, specifically â€œLaw No. 13 of 2003 and Minister of Manpower Regulation No. 6 of 2020â€. The results indicate that interns are legally entitled to a stipend, social security, and labor protections; however, in practice, they are often treated like workers without receiving the rights they deserve. This highlights a gap between regulations and implementation, necessitating more effective oversight and enforcement of the law.